2013
DOI: 10.2298/vsp1304380s
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between subjective and objective nasal breathing assessments in examinees with nasal septum deformities

Abstract: Rhinomanometry significantly correlates with the subjective nose breathing assessment and it can be used as a reliable and objective indicator of nose breathing in everyday clinical practice. Acoustic rhinometry, on the other hand, which does not correlate with a subjective nose breathing assessment could have a greater significance in a scientific sense than in clinical applying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…For nasal obstruction, the most commonly studied PROM was the visual analogue scale (VAS) for nasal obstruction which was used in 45% of the included studies 17,36,40,41,44,48–50,52–60 . Only 25% of the included papers used the validated NOSE questionnaire for nasal obstruction 30,31,35,46,48,50,61,62 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For nasal obstruction, the most commonly studied PROM was the visual analogue scale (VAS) for nasal obstruction which was used in 45% of the included studies 17,36,40,41,44,48–50,52–60 . Only 25% of the included papers used the validated NOSE questionnaire for nasal obstruction 30,31,35,46,48,50,61,62 .…”
Section: Resultsmentioning
confidence: 99%
“…Because the NOSE questionnaire was only validated as a PROM for nasal obstruction due to a deviated septum for patients undergoing septoplasty in 2004, 63 studies conducted prior to 2004 would not have been able to use the questionnaire. Nevertheless, a large number of studies conducted after 2004 opted not to utilize the NOSE questionnaire 17,19,29,35,40–42,44,48,50,53–60 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 in 2009 could not refer to 4-phase-rhinomanometry because at this time statistically relevant logarithmic data have not been available. Savovic et al 9 found recently a correlation between subjective obstruction and rhinomanometric results if the degree of obstruction increases -one more hint for the relation to the logarithmic scale of sensing. In summary, misleading and unfounded statements as they have been recently given by Clement et al 10 and Wong and Eccles 11 have to be rejected because they barricade the way of a meaningful development of nasal airway function tests.…”
Section: Discussionmentioning
confidence: 96%
“…The purpose of this study was to demonstrate the changes of the mucociliary clearance in particular diseases, or to highlight the possible risk factors for its prolonged duration [6][7][8][9] . Rhinitis and chronic rhinosinusitis have an undeniable role in the mucociliary clearance decreased performance, according to a US In a study on patients with deviated septum, who underwent septoplasty intervention, it has been shown that this pathology has a direct effect on the mucociliary clearance and that surgery has good effects in restoration of the mucociliary function in affected patients 10 .…”
Section: Discussionmentioning
confidence: 99%